Speed control of LIM drives using indirect secondary field oriented control - Aditya K. (My University, 2025)
Speed control of linear induction motor becomes complicated due to existence of vertical forces in addition to thrust. In order to gain high performance and adopting LIM for application like HSGT it is necessary to control this vertical force independent of thrust. In the present paper speed control of LIM based drive has been shown using indirect secondary field oriented control (IFOC). Performance of a LIM based conveyor belt system with IFOC method has been shown using a commercially available software package Matlab/Simulink. © 2013 IEEE.